2008
DOI: 10.1128/aac.00724-07
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction between Fosamprenavir-Ritonavir and Rifabutin in Healthy Subjects

Abstract: Rifabutin (RFB) is administered for treatment of tuberculosis and Mycobacterium avium complex infection, including use for patients coinfected with human immunodeficiency virus (HIV).Plasma exposure to RFB and dAc-RFB, both substrates of CYP3A4, has been increased significantly by coadministration with CYP3A4 inhibitors, including HIV protease inhibitors (PIs) (1, 5), which has the potential to increase the risk of RFB-associated adverse events, including neutropenia and uveitis (Mycobutin product information,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 9 publications
4
24
0
Order By: Relevance
“…Previous drug-drug interaction studies between DTG and protease inhibitors have reported no clinically significant alteration in the PK of TPV, atazanavir, darunavir, and lopinavir (4-6). The PK parameters of APV observed in the current study were similar to those presented in previously published data (16,17). Therefore, the results from the current study are consistent with the lack of a significant effect of DTG on the CYP450 enzymes involved in the metabolism of protease inhibitors.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous drug-drug interaction studies between DTG and protease inhibitors have reported no clinically significant alteration in the PK of TPV, atazanavir, darunavir, and lopinavir (4-6). The PK parameters of APV observed in the current study were similar to those presented in previously published data (16,17). Therefore, the results from the current study are consistent with the lack of a significant effect of DTG on the CYP450 enzymes involved in the metabolism of protease inhibitors.…”
Section: Discussionsupporting
confidence: 81%
“…Table 4 lists the mean steady-state plasma PK of APV following coadministration of DTG and FPV-RTV. Amprenavir exposure following coadministration of DTG and FPV-RTV was similar to historical data, suggesting that DTG does not affect APV exposure (16,17).…”
Section: Resultssupporting
confidence: 58%
“…Other studies have also reported an increased AE profile when RFB and boosted PIs are coadministered in healthy volunteers (7,15,28). Similar findings were observed in another study of healthy volunteers receiving a boosted PI and rifampin (3), where the incidence of liver-related AEs was higher than seen in HIV-1-infected patients in routine clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the overall safety profile for DRV/r, no dose adjustment of DRV is considered necessary. Given the safety profile seen with concomitant RFB (150 mg QOD) and a boosted PI in healthy volunteers in this and other studies (7,15,28), it is not recommended to conduct further studies with this combination in healthy volunteers. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation